2017
DOI: 10.1016/j.jamda.2017.03.018
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Robotic Seal as a Therapeutic Tool to Improve Dementia Symptoms: A Cluster-Randomized Controlled Trial

Abstract: Although more effective than usual care in improving mood states and agitation, PARO was only more effective than a plush toy in encouraging engagement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
253
0
12

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 220 publications
(270 citation statements)
references
References 24 publications
5
253
0
12
Order By: Relevance
“…The initial searches identified 2,931 unique papers. Of these, 344 were selected for full‐text review and 19 studies (reported in 27 papers) met the inclusion criteria (see Figure for reasons for exclusion): 10 qualitative studies (Birks, Bodak, Barlas, Harwood, & Pether, ; Chang & Sabanovic, ; Chang, Sabanovic, & Huber, ; Giusti & Marti, ; Gustafsson, Svanberg, & Müllersdorf, ; Iacono & Marti, ; Jung, van der Leij, & Kelders, ; Moyle et al, ; Niemelä, Määttä, & Ylikauppila, ; Pfadenhauer & Dukat, ), 2 mixed methods (randomised trials with qualitative elements), reported across 8 papers (Mervin et al, ; Moyle, ; Moyle, ; Moyle, ; Moyle, ; Moyle, ; Robinson, Macdonald, Kerse, & Broadbent, , ) and seven randomised trials reported in nine papers (Banks, Willoughby, & Banks, ; Joranson, Pedersen, Rokstad, & Ihlebaek, , ; Libin & Cohen‐Mansfield, ; Moyle et al, ; Petersen, Houston, Qin, Tague, & Studley, ; Thodberg, Sorensen, Christensen, et al, ; Thodberg, Sørensen, Videbech, et al, ; Valenti Soler et al, ). An update search, carried out in July 2018 across all databases with de‐duping against those already screened, found no additional included papers or studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The initial searches identified 2,931 unique papers. Of these, 344 were selected for full‐text review and 19 studies (reported in 27 papers) met the inclusion criteria (see Figure for reasons for exclusion): 10 qualitative studies (Birks, Bodak, Barlas, Harwood, & Pether, ; Chang & Sabanovic, ; Chang, Sabanovic, & Huber, ; Giusti & Marti, ; Gustafsson, Svanberg, & Müllersdorf, ; Iacono & Marti, ; Jung, van der Leij, & Kelders, ; Moyle et al, ; Niemelä, Määttä, & Ylikauppila, ; Pfadenhauer & Dukat, ), 2 mixed methods (randomised trials with qualitative elements), reported across 8 papers (Mervin et al, ; Moyle, ; Moyle, ; Moyle, ; Moyle, ; Moyle, ; Robinson, Macdonald, Kerse, & Broadbent, , ) and seven randomised trials reported in nine papers (Banks, Willoughby, & Banks, ; Joranson, Pedersen, Rokstad, & Ihlebaek, , ; Libin & Cohen‐Mansfield, ; Moyle et al, ; Petersen, Houston, Qin, Tague, & Studley, ; Thodberg, Sorensen, Christensen, et al, ; Thodberg, Sørensen, Videbech, et al, ; Valenti Soler et al, ). An update search, carried out in July 2018 across all databases with de‐duping against those already screened, found no additional included papers or studies.…”
Section: Resultsmentioning
confidence: 99%
“…All studies were conducted within the past 15 years. Five studies were conducted in the United States (Banks et al, ; Birks et al, ; Chang & Sabanovic, ; Chang et al, ; Petersen et al, ) and four in Australia (Birks et al, ; Moyle et al, , , ), with the remaining studies taking place in Italy (Giusti & Marti, ; Iacono & Marti, ), New Zealand (Robinson, Macdonald, Kerse, & Broadbent, ), Denmark (Thodberg, Sorensen, Christensen, et al, ), Finland (Niemelä et al, ), Germany (Pfadenhauer & Dukat, ), the Netherlands (Jung et al, ), Norway (Joranson, Pedersen, Rokstad, & Ihlebaek, ), Spain (Valenti Soler et al, ) and Sweden (Gustafsson et al, ). The studies involved more than 800 residents (the total number is not clear as two observation studies did not report the number of residents observed) (Chang & Sabanovic, ; Pfadenhauer & Dukat, ).…”
Section: Resultsmentioning
confidence: 99%
“…10‐min per participant) of 131 participants, from nine Australian long‐term aged care facilities using the EPWDS, were undertaken. These videos were part of a larger project where residents were presented with PARO—a therapeutic, interactive, robotic seal—between 2015 ‐ 2016 (Moyle et al., ). Participants were aged between 61‐101 ( M = 83.97, SD 8.29) and 26.7% were male.…”
Section: The Studymentioning
confidence: 99%
“…However, several studies began reporting the positive impact of SARs on the daily living and quality of life of older people . Many of these studies examined animal‐shaped companion robots and their therapeutic effects on older people . Takayanagi et al .…”
Section: Introductionmentioning
confidence: 99%